2021
DOI: 10.3390/ijerph182111464
|View full text |Cite
|
Sign up to set email alerts
|

Irritable Bowel Syndrome Prevalence among Participants of Woodstock Rock Festival in Poland Based on Rome IV Criteria Questionnaire

Abstract: Background: Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal disorder (FGID), in which etiology and pathogenesis are not fully explored. There is an ongoing need for more population studies adhering to new ROME IV criteria. In the current study, which follows our previous investigation among participants of the Woodstock Rock Festival in Poland, we aimed to evaluate the prevalence of IBS and its relation to age, gender, education, and IBS type. Methods: Rome IV criteria questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The findings are in accordance with previous studies, showing a high prevalence of IBS in the general population ( 28 ). Moreover, the data indicated that psychosocial and sensory factors contributed to self-reported pain in IBS ( 29 ).…”
Section: Discussionsupporting
confidence: 93%
“…The findings are in accordance with previous studies, showing a high prevalence of IBS in the general population ( 28 ). Moreover, the data indicated that psychosocial and sensory factors contributed to self-reported pain in IBS ( 29 ).…”
Section: Discussionsupporting
confidence: 93%
“…A population-based study conducted in the United States, Canada and the United Kingdom based on a self-assessment questionnaire using the Rome IV Diagnostic Questionnaire and Rome III irritable bowel syndrome (IBS), showed a prevalence of IBS ranging from 4.4% to 4.8% [ 57 ]. Another study conducted in Poland, among participants of the 2018 Woodstock Rock Festival using questionnaires based on the Rome IV criteria showed a rate of 11% of IBS [ 58 ]. A cross-sectional study conducted in Riadh in 3 out-patients clinics using self-assessment questionnaires distributed via social media and based on the Rome IV criteria showed a prevalence of 7.9% of IBS [ 59 ].…”
Section: Discussionmentioning
confidence: 99%